Autophagy-mediated clearance of aggresomes is not a universal phenomenon - Wong, Esther S.P. (Oxford University Press, 2008)
Aggresomes are juxtanuclear inclusion bodies that have been proposed to act as staging grounds for the disposal of protein aggregates via the autophagic route. To examine whether the composition of an aggresome influences its clearance by autophagy, we ectopically expressed a variety of aggregation-prone proteins in cultured cells to generate aggresomes that differ in their protein content. We found that whereas aggresomes generated in cells expressing mutant huntingtin or mutant tau, or co-expressing synphilin-1 and α-synuclein, are amenable to clearance by autophagy, those produced in AIMP2 (p38)- or mutant desmin-expressing cells are apparently resistant to autophagic clearance. Notably, AIMP2 (p38)- and desmin-positive inclusions fail to recruit key components of the autophagic/lysosomal system. However, by altering the composition of inclusions, ‘autophagy-resistant’ aggresomes could be rendered ‘autophagy-susceptible’. Taken together, our results demonstrate that not all aggresomes are efficiently primed for autophagic clearance and highlight a certain degree of selectivity for the supposedly non-discriminative pathway.